Assessing Health Status in Cancer Patients Referred for Radiotherapy in Kazakhstan - Aigul Almabek; Dilyara Kaidarova; Berik Issatayev; Magzhan Sadykov; Alena Goncharova (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Cancer is a group of disorders with high mortality. Evaluating cancer patients' perceptions regarding their quality of life is of great importance in observation of these people. The current cross-sectional study aimed to measure health-related quality of life in patients with late-stage cancer and to elicit the components representing greater functional limitations. Materials and methods: Forty patients (29 women and 11 men, mean age: 55.8 years) at late-stage multiple-organ cancer attending for radiation therapy were interviewed. We used the Russian version of 36-Item Short Form Health Survey (SF-36), consisting of 36 multiple-choice questions divided into eight subscales. Results: The participants reported impaired health-related quality of life in all eight aspects, although the scores were above the average value determined for general population. Major disabilities were lying within domains reflecting social functioning (56.88±14.14) and one's ability to perform life roles in the light of cancer impacts on emotional health (54.17±30.84). Conclusion: This research reinforces the importance of psycho-oncology services and social support for cancer survivors besides antitumor therapy. Meanwhile, the quality-of-life assessment could be useful for clinicians in terms of cancer treatment and choosing appropriate rehabilitation strategy. Our findings may have implications for public health and future research.